From Genes to Systems: The Role of Food Supplementation in the Regulation of Sepsis-Induced Inflammation - Cabello-Verrugio, C (Elsevier B.V., 2024)
Systemic inflammation includes a widespread immune response to a harmful stimulus that results in extensive systemic damage. One common example of systemic inflammation is sepsis, which is defined as life-threatening organ dysfunction caused by a dysregulated host response to infection. Under the pro-inflammatory environment of sepsis, oxidative stress contributes to tissue damage due to dysfunctional microcirculation that progressively causes the failure of multiple organs that ultimately triggers death. To address the underlying inflammatory condition in critically ill patients, progress has been made to assess the beneficial effects of dietary supplements, which include polyphenols, amino acids, fatty acids, vitamins, and minerals that are recognized for their immuno-modulating, anticoagulating, and analgesic properties. Therefore, we aimed to review and discuss the contribution of food-derived supplementation in the regulation of inflammation from gene expression to physiological responses and summarize the precedented potential of current therapeutic approaches during systemic inflammation. © 2023